Removal Performance of Tetracycline and Oxytetracycline From Aqueous Solution Via Natural Zeolites: An Equilibrium and Kinetic Study. Issue 10 (13th September 2017) - Lye, Jimmy Wei Ping; Saman, Norasikin; Sharuddin, Siti Shilatul Najwa; Othman, Nurul Sakinah; Mohtar, Safia Syazana; Md Noor, Ahmad Mujahid; Buhari, Junaidah; Cheu, Siew Chin; Kong, Helen; Mat, Hanapi
Abstract : The persistence of antibiotics in sewage wastewater treatment plants in recent years has emerged as a serious issue. This study therefore evaluated three types of natural zeolites (i.e., NZ01, NZ02, and NZ03) for the removal of selected antibiotics namely tetracycline (TC) and oxytetracycline (OTC) from aqueous solution. The physical and chemical properties of the natural zeolites were characterized using various analytical techniques and the antibiotic removal studies were carried out in a batch adsorption experiment evaluated at various experimental conditions. The highest adsorption capacity was 62.5 and 76.3 μmol/g for TC and OTC, respectively, observed for NZ02 at pH values between 7 and 8. The adsorption of TC and OTC followed the Langmuir and Temkin isotherm models, respectively, whereas the adsorption kinetic data obeyed the Elovich kinetic model. The regeneration study on NZ02 indicated that it can still remove TC and OTC after five adsorption/desorption cycles. The removal efficiency of TC and OTC also improved from approximately 5–39 and 28%, respectively, by addition of NZ02 during the coagulation/flocculation process. These results thus demonstrated the applicability of the natural zeolites, especially NZ02, for the removal of TC and OTC from aqueous solution; hence the potential for the application in sewage treatment process for removal of antibiotics through either conventional adsorption/desorption or adsorptive coagulation/flocculation (ACF) process. Abstract : The persistence of antibiotics in wastewater should be resolved to prevent damaging effects to the environment and human health. Natural zeolites are potential cost‐effective adsorbents to remove common antibiotics such as tetracycline (TC) and oxytetracycline (OTC) from sewage wastewater. Parameters affecting the removal of antibiotics via natural zeolites are studyed. The experimental data suggests that TC and OTC can be remove effectively.